2008
DOI: 10.1042/ba20070223
|View full text |Cite
|
Sign up to set email alerts
|

Development of an in vitro reproductive screening assay for novel pharmaceutical compounds

Abstract: An in vitro reproductive cell-based toxicity assay was developed using MLTC-1 (murine Leydig tumour cell line) in order to examine the reproductive toxicity of two novel nanopharmaceutical compounds, namely ethylene glycol mono allyl ether and poly(ethylene glycol) octa-functionalized polyhedral oligomeric silsesquioxane. Three commonly used cytotoxicity assays, namely the MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide], MTS [3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…An extract from a marine snail was significantly cytotoxic to a human Jar choriocarcinoma placental cell line. As the number of viable cells decreased, secreted progesterone increased [77]. Gross et al [78] also described dying primary-derived granulosa cells increasing progesterone production.…”
Section: Discussionmentioning
confidence: 99%
“…An extract from a marine snail was significantly cytotoxic to a human Jar choriocarcinoma placental cell line. As the number of viable cells decreased, secreted progesterone increased [77]. Gross et al [78] also described dying primary-derived granulosa cells increasing progesterone production.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the MTT assay requires extensive incubation periods of anything from 4 to 17 H for the production of the formazan product . MTT incubation periods vary greatly depending on the cell line . The optimized MTT assay for the JAr cell line in the present study adopted a 2 H attachment using 20,000 cells per well, followed by 1 H MTT incubation at a concentration of 0.5 mg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…760 An in vitro study of the reproductive toxicity of poly(ethylene glycol)-substituted POSS cage has been carried out, and the cages were found to be cytotoxic at concentrations of g0.1 µg mL -1 , but human chorionic gonadotropin reduced cytotoxicity to g1000 µg mL -1 . 256 See section 4.4.1 for a further description of the uses of POSS-containing materials with biological applications.…”
Section: Biological Properties and Medical Uses Of Possmentioning
confidence: 99%